ASSESSING THE AWARENESS OF MODERN PEDAGOGY AND PERCEPTION OF ONLINE TEACHING AMONG FACULTY MEMBERS IN COIMBATORE CITY, TAMILNADU (Journal of Pharmaceutical Negative Results, 2023)
The COVID-19 epidemic has interfered with online teaching instruction in a number of countries. It has put to the test whether the academic institutions are ready to handle such a sudden catastrophe. The primary mode of instruction in developing countries like India during the pandemic has switched to online learning in consideration from the traditional mode of teaching. In this regard, the study was conducted among 90 faculty members to evaluate the awareness and perception of online teaching among faculties in Coimbatore District, India. The study was to ascertain how faculty saw online learning. According to the analysis, Zoom, Microsoft Teams, which provides online interactive lessons, and WhatsApp are the most widely used online platforms in India for communicating with students outside of the classroom. Due to COVID-19, online learning can serve as a temporary solution, but it cannot take the place of in-person instruction to a larger extent. The study suggests that using online teaching is to satisfy the need of the hour but a blend of both is demanded in the learning environment.